2023
DOI: 10.1155/2023/9536571
|View full text |Cite
|
Sign up to set email alerts
|

Overflow Effect of COVID-19 Pandemic on Stock Market Performance: A Study Based on Growing Economy

Abstract: Purpose. The purpose of this study is to evaluate the effect that COVID-19 has on the performance of the stock market in emerging economies. The findings as a whole demonstrate that the stock market does not react significantly. We believe that the outcomes of this study provide knowledge that is useful for decision makers in financial markets and policy all around the globe. Methods. Data for 140 companies are obtained from the official websites of the companies listed on the Pakistan Stock Exchange. The Wilc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…[ 18 ] conducted a study to investigate the share market prices are related to specific events and found the significant relationship between them. According to [ 19 ] that the COVID-19 has significant negative and positive impact on the performance of organizations, and they also concluded that some companies maintained their sustainability even though most of the firms suffered from the pandemic. Moreover, [ 20 ] investigated the impact on the COVID-19 on the three different stock markets belong to different region such as Pakistan, China and the USA and found the significant negative relationship between the COVID-19 and stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 18 ] conducted a study to investigate the share market prices are related to specific events and found the significant relationship between them. According to [ 19 ] that the COVID-19 has significant negative and positive impact on the performance of organizations, and they also concluded that some companies maintained their sustainability even though most of the firms suffered from the pandemic. Moreover, [ 20 ] investigated the impact on the COVID-19 on the three different stock markets belong to different region such as Pakistan, China and the USA and found the significant negative relationship between the COVID-19 and stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The growth of infrastructure stimulates economic growth, which further leads to industrialisation and is helpful in economic development [19]. Socioeconomic development is assessed in light of economic conditions and indicators as well [20]. Also of importance are access to healthcare, environmental conditions, and general quality of life [21].…”
Section: Factors Contributing To Growth In Socioeconomic Developmentmentioning
confidence: 99%
“…Recent studies have shown GCG can reduce environmental pollution through improving enterprise performance, motivating innovation and upgrading industrial structure. For example, Du et al (2019) [14] investigated how informal environmental regulation, like public environmental appeal, exerts positive effect on innovation efficiency [15].…”
Section: Introductionmentioning
confidence: 99%